2006
DOI: 10.1074/jbc.m603776200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of Falcipain-2, a Hemoglobinase from the Malarial Parasite Plasmodium falciparum

Abstract: Malaria is caused by protozoan erythrocytic parasites of the Plasmodium genus, with Plasmodium falciparum being the most dangerous and widespread disease-causing species. Falcipain-2 (FP-2) of P. falciparum is a papain-family (C1A) cysteine protease that plays an important role in the parasite life cycle by degrading erythrocyte proteins, most notably hemoglobin. Inhibition of FP-2 and its paralogues prevents parasite maturation, suggesting these proteins may be valuable targets for the design of novel antimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 69 publications
5
84
0
Order By: Relevance
“…Recently, the crystal structure of FP2A complex with an irreversible inhibitor, iodoacetamide, was reported at 3.1A [35]. Interestingly, the crystal structure revealed the presence of four monomers of FP2A in the crystal, consistent with our recent demonstration that the recombinant FP2B, which is a paralog of FP2A, exists as a multimeric enzyme in solution [18,35].…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Recently, the crystal structure of FP2A complex with an irreversible inhibitor, iodoacetamide, was reported at 3.1A [35]. Interestingly, the crystal structure revealed the presence of four monomers of FP2A in the crystal, consistent with our recent demonstration that the recombinant FP2B, which is a paralog of FP2A, exists as a multimeric enzyme in solution [18,35].…”
Section: Resultssupporting
confidence: 70%
“…Recently, the crystal structure of FP2A complex with an irreversible inhibitor, iodoacetamide, was reported at 3.1A [35]. Interestingly, the crystal structure revealed the presence of four monomers of FP2A in the crystal, consistent with our recent demonstration that the recombinant FP2B, which is a paralog of FP2A, exists as a multimeric enzyme in solution [18,35]. Clearly, additional structural studies on falcipains complexed with novel inhibitors will be needed to facilitate ongoing efforts to develop compounds that can selectively target falcipains and show relatively less inhibitory effects on host calpains and other cysteine proteases.…”
Section: Resultsmentioning
confidence: 99%
“…After reduction, these compounds can transfer single electrons to key oxidants of P. falciparum, e.g., to the hemoglobin catabolites methemoglobin and Fe(III)-protoporphyrin IX (22,24,26). The generated Fe(II) species are toxic to the parasite since Fe(II)-containing oxyhemoglobin is a poor substrate of the hemoglobinase falcipain-2 (27), and Fe(II)-protoporphyrin IX was shown to inhibit the crystallization of ␤-hematin in vitro (28). As a result of drug action, NA-DPH is consumed, and damaging Fe(II) species are constantly generated.…”
mentioning
confidence: 99%
“…Further, the structure of falcipain indicates a protruding configuration for the motif, surrounded by a predominant negative charge , and may be charge residues are crucial for interaction with hemoglobin. It has also been demonstrated that falcipain-2 has relatively higher affinity for methemoglobin (kDa is 0.8 lM) than hemoglobin (kDa is 3.3 lM) (Hogg et al 2006). Based on this observation it has been suggested that several factors contribute to the formation of methemoglobin during malarial infection, including an acidic pH of plasmodial food vacuole, oxidative damage in RBC (Akompong et al 2000;Müller 2004), which causes an increase in methemoglobin content up to 20-42% in the plasmodial food vacuole.…”
Section: Function Of Different Domains Of Malarial Proteasesmentioning
confidence: 99%